Maternal Characteristics and the Incidence of Anemia Among Pregnant Women - Badri, Putri Rizki Amalia; Pratiwi, Ratih; Anggina, Dientyah Nur; Ismailsyah, Muhammad; Shahab, Fadhilah Jasmine (Sarana Ilmu Indonesia (salnesia), 2025)
During pregnancy, women are at risk of developing anemia, which can increase the likelihood of preterm birth and, in severe cases, lead to maternal or infant mortality. Anemia in pregnancy is influenced by multiple factors, and identifying these determinants can facilitate effective prevention. This study aimed to determine the prevalence of anemia among pregnant women and the factors associated with it. The research used a cross-sectional design with 100 pregnant women living in the working area of Nagaswidak Public Health Center, Palembang, as subjects. Samples were selected using a consecutive sampling method. Hemoglobin levels were measured using a hemoglobin test strip, while other variables were obtained through questionnaires. Bivariate analysis was conducted using the chi-square test. The results showed that gestational age (p-value=0,032), pregnancy spacing (p-value=0,017), compliance with iron tablet consumption (p-value=0,004), and nutritional status (p-value=0,000) were significantly associated with anemia in pregnant women. Meanwhile, maternal age (p-value=0,064), education (p-value=0,703), occupation (p-value=0,908), parity (p-value=0,444), knowledge (p-value=0,251), and dietary patterns (p-value=0,965) were not significantly related. Efforts to prevent anemia in pregnancy should focus on improving iron tablet compliance, monitoring nutritional status, and promoting optimal pregnancy spacing.